Preparation method of photocatalytic degradation material for treating acephate sewage
By preparing photocatalytic degradation materials for 5-methyl-indole-6-carboxylate/acrylamide gallium coordination polymer, the problem of difficulty in degrading acetylmethylamide sewage in the prior art is solved, and efficient and environmentally friendly sewage treatment effect is achieved.
Patent Information
- Application Number
- CN202510007242.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively degrade acetamide sewage, and traditional water treatment methods have problems of environmental protection and economic benefits.
By preparing a photocatalytic degradation material containing 5-methyl-indole-6-carboxylate/acrylamide gallium complexing polymer, the acetamide sewage was degraded using visible photocatalytic technology.
It realizes efficient visible light catalytic degradation of acetylmethylphosphate sewage, with outstanding visible light catalytic characteristics, significantly improving the efficiency and environmental protection of sewage treatment.
Smart Images

Figure CN119798499A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of acephate wastewater treatment, in particular to a method for preparing a photocatalytic degradation material for treating acephate wastewater. Background Art
[0002] Acephate is an organophosphorus insecticide with broad-spectrum neurotoxicity. It causes nerve excitement and respiratory difficulties in pests and causes their death by acting on the acetylcholinesterase of pests. Compared with the highly toxic organophosphorus insecticide acephate, acephate is less toxic and is widely used to control wheat aphids, wheat midges, leaf rollers, rice planthoppers and other pests of crops such as wheat and rice. It is widely used to kill cabbage worms of vegetables, and is also widely used to control insect pests such as large green leafhoppers, golden moths and longhorn beetles of fruit trees and tea trees. In the process of pest control, only less than 5% of acephate directly acts on pests, and more than 60% of acephate enters the soil and water environment. Acephate is difficult to completely degrade naturally, and it will enter the human body through the food chain, posing a serious threat to humans and the natural environment. The production and application of acephate will lead to the generation of acephate wastewater.
[0003] Photocatalytic materials absorb light energy and can generate electron-hole pairs to produce strongly oxidizing free radicals to oxidatively degrade pollutants adsorbed on the surface. Therefore, using photocatalytic materials to photocatalytically degrade acephate wastewater is a green and environmentally friendly water treatment approach. At present, there is an urgent need to develop a photocatalytic degradation material with excellent visible light catalytic performance and efficient visible light degradation of acephate wastewater. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a photocatalytic degradation material for treating acephate wastewater. The photocatalytic degradation material prepared by the method has outstanding visible light catalytic properties and has the performance of efficient visible light catalytic degradation of acephate-containing wastewater.
[0005] The technical solution adopted by the present invention to solve its technical problem is:
[0006] The present invention provides a method for preparing a photocatalytic degradation material for treating acephate wastewater, comprising the following steps:
[0007] Step [1] preparing 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer;
[0008] Step [2]: loading 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foam copper substrate;
[0009] Step [3] converts the 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foam copper substrate into a poly-5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer.
[0010] Preferably, the step [1] specifically includes the following operations:
[0011] Add 5-methyl-indole-6-carboxylic acid, 2-pyrazinemethanol and trifluoromethanesulfonic acid into deionized water and mix to form a reaction solution; react at room temperature for 18-24 hours, filter to obtain a solid phase product, and dry the solid phase product at 30-40° C. for 5-8 hours to obtain 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer;
[0012] Preferably, per liter of the reaction solution, the amount of 5-methyl-indole-6-carboxylic acid added is 130-160 g, the amount of 2-pyrazinemethanol added is 100-130 g, and the amount of trifluoromethanesulfonic acid added is 40-60 mL.
[0013] Preferably, the step [2] specifically includes the following operations:
[0014] b1. Add 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer, acrylamide, acetonitrile and ethylene chloride to petroleum ether, mix to form an electrodeposition solution, and disperse by ultrasonic for 1.5-2 hours. Then, immerse the foam copper sample in the electrodeposition solution and use it as a cathode, and use a stainless steel electrode as an anode. Electrophoretic deposition is performed at a constant voltage of 30 to 50 V at room temperature for 15 to 30 minutes to obtain a foam copper having 5-methyl-indole-6-carboxylic acid pyrazine methyl ester and acrylamide deposited on the surface, which is recorded as intermediate A.
[0015] b2. Add 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer, acrylamide, 5-methyl-indole-6-carboxylic acid and sodium azobiscyanovalerate to deionized water and mix to form a polymerization solution; immerse the intermediate A in the polymerization solution, react at room temperature for 24-28 hours, and dry at room temperature for 6-8 hours to obtain a foam copper with a surface loaded with 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer, which is recorded as intermediate B.
[0016] Preferably, in step b1, the amount of 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer added per liter of the electrodeposition solution is 60-90 g, the amount of acrylamide added is 40-70 g, the amount of acetonitrile added is 20-30 mL, and the amount of ethylene chloride added is 10-40 ml; the weight of the foamed copper immersed in each liter of the electrodeposition solution is 190-210 g.
[0017] Preferably, in step b2, the amount of 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer added per liter of the polymerization solution is 10-30 g, the amount of acrylamide added is 30-50 g, the amount of 5-methyl-indole-6-carboxylic acid added is 40-60 g, and the amount of sodium azobiscyanovalerate added is 10-20 g; the weight of the intermediate A immersed in each liter of the polymerization solution is 260-300 g.
[0018] Preferably, the step [3] specifically includes the following operations:
[0019] c1. Gallium trichloride, 2-pyrazinemethanol and sodium bisulfite were added to deionized water and mixed to form a conversion solution;
[0020] c2. Immerse the intermediate B in the conversion solution, heat in a water bath to 50-70° C., react for 12-14 hours, wash with deionized water, and dry at room temperature for 8-12 hours to obtain a copper foam with a surface loaded with poly-5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer, which is the photocatalytic degradation material.
[0021] Preferably, in step c1, the amount of gallium trichloride added to each liter of the conversion solution is 70-100 g, the amount of 2-pyrazinemethanol added is 25-50 g, and the amount of sodium bisulfite added is 10-25 g.
[0022] Preferably, in step c2, the weight of the intermediate B immersed in each liter of the conversion liquid is 150-200 g.
[0023] The positive effects of the present invention are as follows: the photocatalytic degradation material prepared by the method of the present invention loads a poly (5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) gallium coordination polymer on the surface of the foamed copper, wherein two oxygen atoms of two carbonyl groups of a (5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) polymer molecular chain provide lone pairs of electrons to be shared with gallium atoms, each gallium atom forms four coordination bonds with four oxygen atoms of four carbonyl groups of two (5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) polymer molecular chains, and a coordination polymer with a ring structure is formed between each gallium atom and the (5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) polymer ligand. Based on this, the (5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) polymer has a delocalized π bond, which can facilitate the migration of photogenerated holes and photogenerated electrons, and increase its conductivity in the photocatalytic process; at the same time, the pyrazine of the (5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) polymer has a strong adsorption tendency for acephate; in addition, the (5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) gallium coordination polymer is a coordination polymer with narrow bandgap semiconductor properties. When visible light irradiates the (5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) gallium coordination polymer on the surface of the foam copper, the photogenerated electrons react with O2 adsorbed on the surface of the coordination polymer to generate peroxyl radicals · O2-, and the photogenerated holes react with H2O on the surface of the coordination polymer to generate hydroxyl · OH, thereby achieving effective degradation of acephate.
[0024] In summary, the photocatalytic degradation material prepared according to the present invention has outstanding visible light catalytic properties and has the performance of highly efficient visible light catalytic degradation of acephate-containing wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the preparation process of the photocatalytic degradation material of the present invention;
[0026] Figure 2 is a schematic diagram of the microstructure of the photocatalytic degradation material of the present invention;
[0027] Figure 3 The relative concentration of residual acephate in the simulated acephate-containing sewage treated under different conditions in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;
[0028] Figure 4 The hydroxyl radical concentrations of the simulated acephate-containing wastewater treated under different conditions are shown in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0029] Reference Figure 1The present invention provides a method for preparing a photocatalytic degradation material for treating acephate wastewater, comprising the following steps:
[0030] Step [1] prepares 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer, specifically comprising the following operations:
[0031] 5-methyl-indole-6-carboxylic acid, 2-pyrazinemethanol and trifluoromethanesulfonic acid are added to deionized water and mixed to form a reaction solution (wherein the amount of 5-methyl-indole-6-carboxylic acid added per liter of the reaction solution is 130-160 g, the amount of 2-pyrazinemethanol added is 100-130 g, and the amount of trifluoromethanesulfonic acid added is 40-60 mL); react at room temperature for 18-24 hours, filter to obtain a solid phase product, and dry the solid phase product at 30-40° C. for 5-8 hours to obtain a 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer; the reaction process involved is that 5-methyl-indole-6-carboxylic acid reacts with 2-pyrazinemethanol to generate a 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer, and the specific reaction formula is:
[0032]
[0033] Step [2] loading 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foam copper substrate specifically comprises the following operations:
[0034] b1. Add petroleum ether to 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer, acrylamide, acetonitrile and ethylene chloride to form an electrodeposition solution (wherein the amount of 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer added per liter of the electrodeposition solution is 60 to 90 g, the amount of acrylamide added is 40 to 70 g, the amount of acetonitrile added is 20 to 30 mL, and the amount of ethylene chloride added is 10 to 40 ml), ultrasonically dispersed for 1.5-2 hours, and then immersed in the foam copper sample The copper foam is immersed in an electrodeposition solution and used as a cathode (the weight of the copper foam immersed in each liter of the electrodeposition solution is 190-210 g), and a stainless steel electrode is used as an anode. Electrophoretic deposition is performed at a constant voltage of 30-50 V at room temperature for 15-30 minutes to obtain a copper foam with 5-methyl-indole-6-carboxylic acid pyrazine methyl ester and acrylamide deposited on the surface (two monomers, 5-methyl-indole-6-carboxylic acid pyrazine methyl ester and acrylamide, are deposited on the surface of the copper foam by electrodeposition), which is recorded as intermediate A;
[0035] b2. Add 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer, acrylamide, 5-methyl-indole-6-carboxylic acid and sodium azobiscyanovalerate to deionized water and mix to form a polymer solution (wherein the amount of 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer added per liter of the polymer solution is 10-30g, the amount of acrylamide added is 30-50g, the amount of 5-methyl-indole-6-carboxylic acid added is 40-60g, and the amount of sodium azobiscyanovalerate added is 10-20g); immerse the intermediate A in the polymer solution (the weight of the intermediate A immersed in each liter of the polymer solution is 260-300g), react at room temperature for 24-28 hours, and dry at room temperature for 6-8 hours to obtain a foam copper with a surface loaded with 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer, which is recorded as intermediate B. The reaction process of this step involves three reactions that occur continuously:
[0036] (1) 5-methyl-indole-6-carboxylic acid reacts with acrylamide to generate 5-methyl-indole-6-acrylamide. The specific reaction formula is:
[0037]
[0038] (2) 5-methyl-indole-6-acrylamide polymerization reaction generates 5-methyl-indole-6-acrylamide polymerization monomer, and the specific reaction formula is:
[0039]
[0040] (3) A 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer and a 5-methyl-indole-6-polyacrylamide polymerization monomer are polymerized to generate a (5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) polymer, wherein the structure of the (5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) polymer is:
[0041]
[0042] Step [3] converting the 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foam copper substrate into a poly-5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer, specifically comprising the following operations:
[0043] c1. Gallium trichloride, 2-pyrazinemethanol and sodium bisulfite are added to deionized water and mixed to form a conversion solution, wherein the amount of gallium trichloride added per liter of the conversion solution is 70 to 100 g, the amount of 2-pyrazinemethanol added is 25 to 50 g, and the amount of sodium bisulfite added is 10 to 25 g;
[0044] c2. Immerse the intermediate B in the conversion solution (the weight of the intermediate B immersed in each liter of the conversion solution is 150-200 g), heat to 50-70 ° C in a water bath, react for 12-14 hours, wash with deionized water, and dry at room temperature for 8-12 hours to obtain a foam copper with a surface loaded with poly-5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer, which is the photocatalytic degradation material, and its microstructure schematic diagram is as shown Figure 2 Wherein, the structural formula of the poly-5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer is:
[0045]
[0046] The preferred embodiments of the present invention are described below by way of example.
[0047] Example 1
[0048] Preferred embodiment 1 of the present invention provides a method for preparing a photocatalytic degradation material for treating acephate wastewater, comprising the following steps:
[0049] Step [1] prepares 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer, specifically comprising the following operations:
[0050] 5-methyl-indole-6-carboxylic acid, 2-pyrazinemethanol and trifluoromethanesulfonic acid are added to deionized water and mixed to form a reaction solution (wherein the amount of 5-methyl-indole-6-carboxylic acid added is 150 g, the amount of 2-pyrazinemethanol added is 120 g, and the amount of trifluoromethanesulfonic acid added is 50 mL per liter of the reaction solution); react at room temperature for 22 hours, filter to obtain a solid phase product, and dry the solid phase product at 40° C. for 6 hours to obtain 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer;
[0051] Step [2] loading 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foam copper substrate specifically comprises the following operations:
[0052] b1. 5-methyl-indole-6-pyrazine-methyl formate monomer, acrylamide, acetonitrile and vinyl chloride were added to petroleum ether to form an electrodeposition solution (wherein the amount of 5-methyl-indole-6-pyrazine-methyl formate monomer added per liter of the electrodeposition solution was 80 g, the amount of acrylamide added was 60 g, the amount of acetonitrile added was 30 mL, and the amount of vinyl chloride added was 30 ml), ultrasonic dispersion was performed for 2 hours, and then the foamed copper sample was immersed in the electrodeposition solution and used as a cathode (the weight of the foamed copper immersed in the electrodeposition solution per liter was 200 g), a stainless steel electrode was used as an anode, and electrophoretic deposition was performed at a constant voltage of 40 V at room temperature for 25 minutes to obtain a foamed copper having 5-methyl-indole-6-pyrazine-methyl formate and acrylamide deposited on the surface, which was recorded as intermediate A;
[0053] b2. 5-methyl-indole-6-pyrazine carboxylate monomer, acrylamide, 5-methyl-indole-6-carboxylic acid and sodium azobiscyanovalerate were added to deionized water and mixed to form a polymer solution (wherein the amount of 5-methyl-indole-6-pyrazine carboxylate monomer added per liter of the polymer solution was 25g, the amount of acrylamide added was 40g, the amount of 5-methyl-indole-6-carboxylic acid added was 60g, and the amount of sodium azobiscyanovalerate added was 15g); the intermediate A was immersed in the polymer solution (the weight of the intermediate A immersed in the polymer solution per liter was 290g), the reaction was carried out at room temperature for 27 hours, and the surface was dried at room temperature for 7 hours to obtain a foamed copper with 5-methyl-indole-6-pyrazine carboxylate / acrylamide polymer loaded on the surface, which was recorded as intermediate B.
[0054] Step [3] converting the 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foam copper substrate into a poly-5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer, specifically comprising the following operations:
[0055] c1. Gallium trichloride, 2-pyrazinemethanol and sodium bisulfite were added to deionized water and mixed to form a conversion solution, wherein the amount of gallium trichloride added per liter of the conversion solution was 90 g, the amount of 2-pyrazinemethanol added was 40 g, and the amount of sodium bisulfite added was 20 g;
[0056] c2. The intermediate B is immersed in the conversion solution (the weight of the intermediate B immersed in each liter of the conversion solution is 180 g), heated to 60° C. in a water bath, reacted for 13 hours, washed with deionized water, and dried at room temperature for 10 hours to obtain a foam copper with a surface loaded with poly 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer, which is the photocatalytic degradation material, recorded as Example 1.
[0057] Comparative Example 1
[0058] This comparative example 1 provides a method for preparing a photocatalytic degradation material for treating acephate wastewater, comprising the following steps:
[0059] Step [1] prepares 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer, specifically comprising the following operations:
[0060] 5-methyl-indole-6-carboxylic acid, 2-pyrazinemethanol and trifluoromethanesulfonic acid are added to deionized water and mixed to form a reaction solution (wherein the amount of 5-methyl-indole-6-carboxylic acid added per liter of the reaction solution is 140 g, the amount of 2-pyrazinemethanol added is 120 g, and the amount of trifluoromethanesulfonic acid added is 50 mL); react at room temperature for 20 hours, filter to obtain a solid phase product, and dry the solid phase product at 35° C. for 6 hours to obtain 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer;
[0061] Step [2] loading 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foam copper substrate specifically comprises the following operations:
[0062] b1. 5-methyl-indole-6-pyrazine-methyl formate monomer, acrylamide, acetonitrile and vinyl chloride were added to petroleum ether to form an electrodeposition solution (wherein the amount of 5-methyl-indole-6-pyrazine-methyl formate monomer added per liter of the electrodeposition solution was 70 g, the amount of acrylamide added was 60 g, the amount of acetonitrile added was 25 mL, and the amount of vinyl chloride added was 20 ml), ultrasonic dispersion was performed for 1.5 hours, and then the foamed copper sample was immersed in the electrodeposition solution and used as a cathode (the weight of the foamed copper immersed in the electrodeposition solution per liter was 195 g), a stainless steel electrode was used as an anode, and electrophoretic deposition was performed at a constant voltage of 40 V at room temperature for 20 minutes to obtain a foamed copper having 5-methyl-indole-6-pyrazine-methyl formate and acrylamide deposited on the surface, which was recorded as intermediate A;
[0063] b2. Add 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer, acrylamide, 5-methyl-indole-6-carboxylic acid and sodium azobiscyanovalerate to deionized water and mix to form a polymer solution (wherein the amount of 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer added per liter of the polymer solution is 20g, the amount of acrylamide added is 40g, the amount of 5-methyl-indole-6-carboxylic acid added is 50g, and the amount of sodium azobiscyanovalerate added is 15g); the intermediate A is immersed in the polymer solution (the weight of the intermediate A immersed in the polymer solution per liter is 280g), reacted at room temperature for 24 hours, dried at room temperature for 7 hours, and a foam copper having a surface load of 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer is obtained, which is recorded as Comparative Example 1.
[0064] Comparative Example 2
[0065] This comparative example 2 provides a method for preparing a photocatalytic degradation material for treating acephate wastewater, comprising the following steps:
[0066] Step [1] prepares 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer, specifically comprising the following operations:
[0067] 5-methyl-indole-6-carboxylic acid, 2-pyrazinemethanol and trifluoromethanesulfonic acid are added to deionized water and mixed to form a reaction solution (wherein the amount of 5-methyl-indole-6-carboxylic acid added is 150 g, the amount of 2-pyrazinemethanol added is 120 g, and the amount of trifluoromethanesulfonic acid added is 45 mL per liter of the reaction solution); react at room temperature for 22 hours, filter to obtain a solid phase product, and dry the solid phase product at 35° C. for 6 hours to obtain 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer;
[0068] Step [2] loading 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foamed iron substrate specifically comprises the following operations:
[0069] b1. 5-methyl-indole-6-pyrazine-methyl-formate monomer, acrylamide, acetonitrile and vinyl chloride are added to petroleum ether, mixed to form an electrodeposition solution (wherein per liter of the electrodeposition solution, 5-methyl-indole-6-pyrazine-methyl-formate monomer addition amount is 70g, acrylamide addition amount is 60g, acetonitrile addition amount is 24mL, and vinyl chloride addition amount is 20ml), ultrasonic dispersion 2 hours, then the foamed iron sample is immersed in the electrodeposition solution and as a cathode (the weight of the foamed iron immersed in per liter of the electrodeposition solution is 200g), a stainless steel electrode is an anode, and electrophoretic deposition is carried out at a constant voltage of 35V for 25 minutes at room temperature to obtain a foamed iron with 5-methyl-indole-6-pyrazine-methyl-formate and acrylamide deposited on the surface, which is denoted as intermediate D;
[0070] b2. 5-methyl-indole-6-pyrazine-methyl carboxylate monomer, acrylamide, 5-methyl-indole-6-carboxylic acid and sodium azobiscyanovalerate are added to deionized water, mixed to form a polymer solution (wherein per liter of the polymer solution, 5-methyl-indole-6-pyrazine-methyl carboxylate monomer addition amount is 20g, acrylamide addition amount is 45g, 5-methyl-indole-6-carboxylic acid addition amount is 50g, and sodium azobiscyanovalerate addition amount is 18g); the intermediate D is immersed in the polymer solution (the weight of the intermediate D immersed in per liter of the polymer solution is 290g), the reaction is carried out at room temperature for 26 hours, and the foamed iron having 5-methyl-indole-6-pyrazine-methyl carboxylate / acrylamide polymer is obtained, which is designated as intermediate E.
[0071] Step [3] converting the 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foamed iron substrate into a poly-5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer, specifically comprising the following operations:
[0072] c1. Gallium trichloride, 2-pyrazinemethanol and sodium bisulfite were added to deionized water and mixed to form a conversion solution, wherein the amount of gallium trichloride added per liter of the conversion solution was 90 g, the amount of 2-pyrazinemethanol added was 40 g, and the amount of sodium bisulfite added was 20 g;
[0073] c2. The intermediate E is immersed in the conversion solution (the weight of the intermediate E immersed in each liter of the conversion solution is 180 g), heated to 55° C. in a water bath, reacted for 13 hours, washed with deionized water, and dried at room temperature for 13 hours to obtain foam iron with a surface loaded with poly 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer, which is recorded as Comparative Example 2.
[0074] In order to analyze the photocatalytic performance of Example 1, Comparative Example 1 and Comparative Example 2 and the performance of photocatalytic degradation of acephate sewage, acephate was added to deionized water to form a simulated acephate-containing sewage with a concentration of 50 mg / L of acephate. 100 ml of simulated acephate-containing sewage was poured into a beaker, 30 g of Example 1, Comparative Example 1 and Comparative Example 2 were placed in a beaker, and 500 W xenon light was used to irradiate Comparative Example 1, Comparative Example 2 and Example 1 for one hour under visible light with a wavelength of 500 nm and ultraviolet light with a wavelength of 300 nm. The residual acephate concentration and hydroxyl radical concentration of the simulated acephate-containing sewage photocatalytic degradation process were measured by high performance liquid chromatography (a dark control group without light was set at the same time), and the results are as follows: Figure 3 and Figure 4 Shown by: Figure 3 It can be seen that the relative concentrations of residual acephate after 1 hour of the simulated acephate-containing sewage degradation by visible light catalysis and ultraviolet light catalysis in Example 1 were only 0.07 and 0.05, respectively, which were significantly lower than the relative concentrations of residual acephate in Comparative Example 1 under the same treatment conditions (0.64 and 0.52, respectively), and also lower than the relative concentrations of residual acephate in Comparative Example 2 under the same treatment conditions (0.26 and 0.22, respectively); Figure 3 It can be seen that the hydroxyl radical concentrations of Example 1 after 1 hour of simulated degradation of acephate-containing wastewater by visible light catalysis and ultraviolet light catalysis were 876 μmol / L and 897 μmol / L, respectively, which were significantly higher than the hydroxyl radical concentrations of 124 μmol / L and 130 μmol / L of Comparative Example 1 after 1 hour of simulated degradation of acephate-containing wastewater under the same conditions, and also higher than the hydroxyl radical concentrations of 357 μmol / L and 370 μmol / L of Comparative Example 2 under the same conditions.
[0075] The photocatalytic degradation material prepared in Example 1 of the present invention has a strong chemical synergistic effect between the foam copper matrix and the poly (5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) gallium coordination polymer, which effectively broadens the absorption wavelength range of the poly (5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) gallium coordination polymer. At the same time, the highest occupied molecular orbital (HOMO) of the poly (5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) gallium coordination polymer also promotes the transfer of electrons in the foam copper matrix to form a copper ion / poly (5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) gallium coordination polymer interface region, promotes the generation of photogenerated electrons and holes, and thus significantly improves the photocatalytic degradation performance of Example 1. In contrast, the foam iron-based poly (5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) gallium coordination polymer material prepared in Comparative Example 2 has limited ability to catalyze the degradation of acephate wastewater, because:
[0076] (1) The foamed iron base cannot broaden the absorption wavelength range of the poly(5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) gallium coordination polymer material;
[0077] (2) The foamed iron does not have the ability to promote the generation of photogenerated electrons and holes in the photocatalytic reaction of poly(5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide) gallium coordination polymer materials, nor does it have the ability to inhibit the recombination of photogenerated electrons and holes.
[0078] In summary, the photocatalytic degradation material prepared according to the present invention has outstanding visible light catalytic properties and has the performance of highly efficient visible light catalytic degradation of acephate-containing wastewater.
[0079] To illustrate in further detail, three additional examples are provided below.
[0080] Example 2
[0081] Preferred embodiment 2 of the present invention provides a method for preparing a photocatalytic degradation material for treating acephate wastewater, comprising the following steps:
[0082] Step [1] prepares 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer, specifically comprising the following operations:
[0083] 5-methyl-indole-6-carboxylic acid, 2-pyrazinemethanol and trifluoromethanesulfonic acid are added to deionized water and mixed to form a reaction solution (wherein the amount of 5-methyl-indole-6-carboxylic acid added is 130 g, the amount of 2-pyrazinemethanol added is 130 g, and the amount of trifluoromethanesulfonic acid added is 40 mL per liter of the reaction solution); react at room temperature for 18 hours, filter to obtain a solid phase product, and dry the solid phase product at 40° C. for 5 hours to obtain 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer;
[0084] Step [2] loading 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foam copper substrate specifically comprises the following operations:
[0085] b1. 5-methyl-indole-6-pyrazine-methyl formate monomer, acrylamide, acetonitrile and ethylene chloride are added to petroleum ether to form an electrodeposition solution (wherein the amount of 5-methyl-indole-6-pyrazine-methyl formate monomer added per liter of the electrodeposition solution is 60g, the amount of acrylamide added is 40g, the amount of acetonitrile added is 30mL, and the amount of ethylene chloride added is 10ml), ultrasonic dispersion for 1.5 hours, and then the foam copper sample is immersed in the electrodeposition solution and used as a cathode (the weight of the foam copper immersed in each liter of the electrodeposition solution is 190g), a stainless steel electrode is used as an anode, and electrophoretic deposition is performed at a constant voltage of 30V for 30 minutes at room temperature to obtain a foam copper having 5-methyl-indole-6-pyrazine-methyl formate and acrylamide deposited on the surface, which is recorded as intermediate A;
[0086] b2. 5-methyl-indole-6-pyrazine carboxylate monomer, acrylamide, 5-methyl-indole-6-carboxylic acid and sodium azobiscyanovalerate are added to deionized water and mixed to form a polymer solution (wherein the addition amount of 5-methyl-indole-6-pyrazine carboxylate monomer per liter of the polymer solution is 10g, the addition amount of acrylamide is 50g, the addition amount of 5-methyl-indole-6-carboxylic acid is 40g, and the addition amount of sodium azobiscyanovalerate is 10g); the intermediate A is immersed in the polymer solution (the weight of the intermediate A immersed in the polymer solution per liter is 260g), the reaction is carried out at room temperature for 24 hours, and the reaction is dried at room temperature for 6 hours to obtain a foamed copper having a surface load of 5-methyl-indole-6-pyrazine carboxylate / acrylamide polymer, which is recorded as intermediate B.
[0087] Step [3] converting the 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foam copper substrate into a poly-5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer, specifically comprising the following operations:
[0088] c1. Gallium trichloride, 2-pyrazinemethanol and sodium bisulfite were added to deionized water and mixed to form a conversion solution, wherein the amount of gallium trichloride added per liter of the conversion solution was 70 g, the amount of 2-pyrazinemethanol added was 25 g, and the amount of sodium bisulfite added was 10 g;
[0089] c2. The intermediate B is immersed in the conversion solution (the weight of the intermediate B immersed in each liter of the conversion solution is 150 g), heated to 50° C. in a water bath, reacted for 14 hours, washed with deionized water, and dried at room temperature for 8 hours to obtain a foam copper with a surface loaded with poly-5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer, which is the photocatalytic degradation material.
[0090] Example 3
[0091] Preferred embodiment 3 of the present invention provides a method for preparing a photocatalytic degradation material for treating acephate wastewater, comprising the following steps:
[0092] Step [1] prepares 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer, specifically comprising the following operations:
[0093] 5-methyl-indole-6-carboxylic acid, 2-pyrazinemethanol and trifluoromethanesulfonic acid are added to deionized water and mixed to form a reaction solution (wherein the amount of 5-methyl-indole-6-carboxylic acid added per liter of the reaction solution is 160 g, the amount of 2-pyrazinemethanol added is 100 g, and the amount of trifluoromethanesulfonic acid added is 60 mL); react at room temperature for 24 hours, filter to obtain a solid phase product, and dry the solid phase product at 30° C. for 8 hours to obtain 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer;
[0094] Step [2] loading 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foam copper substrate specifically comprises the following operations:
[0095] b1. 5-methyl-indole-6-pyrazine-methyl formate monomer, acrylamide, acetonitrile and vinyl chloride were added to petroleum ether to form an electrodeposition solution (wherein the amount of 5-methyl-indole-6-pyrazine-methyl formate monomer added per liter of the electrodeposition solution was 90g, the amount of acrylamide added was 70g, the amount of acetonitrile added was 20mL, and the amount of vinyl chloride added was 40ml), ultrasonic dispersion was performed for 2 hours, and then the foamed copper sample was immersed in the electrodeposition solution and used as a cathode (the weight of the foamed copper immersed in the electrodeposition solution per liter was 210g), a stainless steel electrode was used as an anode, and electrophoretic deposition was performed at a constant voltage of 50V for 15 minutes at room temperature to obtain a foamed copper having 5-methyl-indole-6-pyrazine-methyl formate and acrylamide deposited on the surface, which was recorded as intermediate A;
[0096] b2. 5-methyl-indole-6-pyrazine carboxylate monomer, acrylamide, 5-methyl-indole-6-carboxylic acid and sodium azobiscyanovalerate are added to deionized water and mixed to form a polymer solution (wherein the 5-methyl-indole-6-pyrazine carboxylate monomer added in an amount of 30g, the acrylamide added in an amount of 30g, the 5-methyl-indole-6-carboxylic acid added in an amount of 60g, and the sodium azobiscyanovalerate added in an amount of 20g per liter of the polymer solution); the intermediate A is immersed in the polymer solution (the weight of the intermediate A immersed in the polymer solution per liter is 300g), the reaction is carried out at room temperature for 28 hours, and the reaction is dried at room temperature for 8 hours to obtain a foamed copper having a surface load of 5-methyl-indole-6-pyrazine carboxylate / acrylamide polymer, which is recorded as intermediate B.
[0097] Step [3] converting the 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foam copper substrate into a poly-5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer, specifically comprising the following operations:
[0098] c1. Gallium trichloride, 2-pyrazinemethanol and sodium bisulfite were added to deionized water and mixed to form a conversion solution, wherein the amount of gallium trichloride added per liter of the conversion solution was 100 g, the amount of 2-pyrazinemethanol added was 50 g, and the amount of sodium bisulfite added was 25 g;
[0099] c2. Immerse the intermediate B in the conversion solution (the weight of the intermediate B immersed in each liter of the conversion solution is 200 g), heat it to 70° C. in a water bath, react for 12 hours, wash with deionized water, and dry at room temperature for 12 hours to obtain a foam copper with a surface loaded with poly 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer, which is the photocatalytic degradation material.
[0100] Example 4
[0101] Preferred embodiment 4 of the present invention provides a method for preparing a photocatalytic degradation material for treating acephate wastewater, comprising the following steps:
[0102] Step [1] prepares 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer, specifically comprising the following operations:
[0103] 5-methyl-indole-6-carboxylic acid, 2-pyrazinemethanol and trifluoromethanesulfonic acid are added to deionized water and mixed to form a reaction solution (wherein the amount of 5-methyl-indole-6-carboxylic acid added per liter of the reaction solution is 145 g, the amount of 2-pyrazinemethanol added is 115 g, and the amount of trifluoromethanesulfonic acid added is 50 mL); react at room temperature for 21 hours, filter to obtain a solid phase product, and dry the solid phase product at 35° C. for 6 hours to obtain 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer;
[0104] Step [2] loading 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foam copper substrate specifically comprises the following operations:
[0105] b1. 5-methyl-indole-6-pyrazine-methyl formate monomer, acrylamide, acetonitrile and vinyl chloride are added to petroleum ether to form an electrodeposition solution (wherein the amount of 5-methyl-indole-6-pyrazine-methyl formate monomer added per liter of the electrodeposition solution is 75g, the amount of acrylamide added is 55g, the amount of acetonitrile added is 25mL, and the amount of vinyl chloride added is 25ml), ultrasonic dispersion for 1.9 hours, and then the foamed copper sample is immersed in the electrodeposition solution and used as a cathode (the weight of the foamed copper immersed in each liter of the electrodeposition solution is 200g), a stainless steel electrode is an anode, and electrophoretic deposition is performed at a constant voltage of 40V for 24 minutes at room temperature to obtain a foamed copper having 5-methyl-indole-6-pyrazine-methyl formate and acrylamide deposited on the surface, which is recorded as intermediate A;
[0106] b2. 5-methyl-indole-6-pyrazine carboxylate monomer, acrylamide, 5-methyl-indole-6-carboxylic acid and sodium azobiscyanovalerate are added to deionized water and mixed to form a polymer solution (wherein the addition amount of 5-methyl-indole-6-pyrazine carboxylate monomer per liter of the polymer solution is 20g, the addition amount of acrylamide is 40g, the addition amount of 5-methyl-indole-6-carboxylic acid is 50g, and the addition amount of sodium azobiscyanovalerate is 15g); the intermediate A is immersed in the polymer solution (the weight of the intermediate A immersed in the polymer solution per liter is 280g), the reaction is carried out at room temperature for 26 hours, and the reaction is dried at room temperature for 7 hours to obtain a foamed copper having a surface load of 5-methyl-indole-6-pyrazine carboxylate / acrylamide polymer, which is recorded as intermediate B.
[0107] Step [3] converting the 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foam copper substrate into a poly-5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer, specifically comprising the following operations:
[0108] c1. Gallium trichloride, 2-pyrazinemethanol and sodium bisulfite were added to deionized water and mixed to form a conversion solution, wherein the amount of gallium trichloride added per liter of the conversion solution was 85 g, the amount of 2-pyrazinemethanol added was 40 g, and the amount of sodium bisulfite added was 16 g;
[0109] c2. The intermediate B is immersed in the conversion solution (the weight of the intermediate B immersed in each liter of the conversion solution is 175 g), heated to 60° C. in a water bath, reacted for 13 hours, washed with deionized water, and dried at room temperature for 10 hours to obtain a foam copper with a surface loaded with poly-5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer, which is the photocatalytic degradation material.
[0110] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a photocatalytic degradation material for treating acephate wastewater, characterized in that: The following steps are included: Step [1] preparing 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer; Step [2]: loading 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foam copper substrate; Step [3] converts the 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer on the surface of the foam copper substrate into a poly-5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer.
2. The method for preparing a photocatalytic degradation material for treating acephate wastewater according to claim 1, characterized in that: The step [1] specifically includes the following operations: 5-methyl-indole-6-carboxylic acid, 2-pyrazinemethanol and trifluoromethanesulfonic acid are added to deionized water and mixed to form a reaction solution; the mixture is reacted at room temperature for 18-24 hours, and a solid phase product is obtained by filtering. The solid phase product is dried at 30-40° C. for 5-8 hours to obtain a 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer.
3. The method for preparing a photocatalytic degradation material for treating acephate wastewater according to claim 2, characterized in that: The amount of 5-methyl-indole-6-carboxylic acid added to each liter of the reaction solution is 130-160 g, the amount of 2-pyrazinemethanol added is 100-130 g, and the amount of trifluoromethanesulfonic acid added is 40-60 mL.
4. The method for preparing a photocatalytic degradation material for treating acephate wastewater according to claim 1, characterized in that: The step [2] specifically includes the following operations: b1. Add 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer, acrylamide, acetonitrile and ethylene chloride to petroleum ether, mix to form an electrodeposition solution, and disperse by ultrasonic for 1.5-2 hours. Then, immerse the foam copper sample in the electrodeposition solution and use it as a cathode, and use a stainless steel electrode as an anode. Electrophoretic deposition is performed at a constant voltage of 30 to 50 V at room temperature for 15 to 30 minutes to obtain a foam copper having 5-methyl-indole-6-carboxylic acid pyrazine methyl ester and acrylamide deposited on the surface, which is recorded as intermediate A. b2. Add 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer, acrylamide, 5-methyl-indole-6-carboxylic acid and sodium azobiscyanovalerate to deionized water and mix to form a polymerization solution; immerse the intermediate A in the polymerization solution, react at room temperature for 24-28 hours, and dry at room temperature for 6-8 hours to obtain a foam copper with a surface loaded with 5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide polymer, which is recorded as intermediate B.
5. The method for preparing a photocatalytic degradation material for treating acephate wastewater according to claim 4, characterized in that: In step b1, the amount of 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer added to each liter of the electrodeposition solution is 60-90g, the amount of acrylamide added is 40-70g, the amount of acetonitrile added is 20-30mL, and the amount of ethylene chloride added is 10-40ml; the weight of the foamed copper immersed in each liter of the electrodeposition solution is 190-210g.
6. The method for preparing a photocatalytic degradation material for treating acephate wastewater according to claim 4, characterized in that: In step b2, the amount of 5-methyl-indole-6-carboxylic acid pyrazine methyl ester monomer added per liter of the polymerization solution is 10-30 g, the amount of acrylamide added is 30-50 g, the amount of 5-methyl-indole-6-carboxylic acid added is 40-60 g, and the amount of sodium azobiscyanovalerate added is 10-20 g; the weight of the intermediate A immersed in each liter of the polymerization solution is 260-300 g.
7. The method for preparing a photocatalytic degradation material for treating acephate wastewater according to claim 1, characterized in that: The step [3] specifically includes the following operations: c1. Gallium trichloride, 2-pyrazinemethanol and sodium bisulfite were added to deionized water and mixed to form a conversion solution; c2. Immerse the intermediate B in the conversion solution, heat in a water bath to 50-70° C., react for 12-14 hours, wash with deionized water, and dry at room temperature for 8-12 hours to obtain a copper foam with a surface loaded with poly-5-methyl-indole-6-carboxylic acid pyrazine methyl ester / acrylamide gallium coordination polymer, which is the photocatalytic degradation material.
8. The method for preparing a photocatalytic degradation material for treating acephate wastewater according to claim 7, characterized in that: In step c1, the amount of gallium trichloride added to each liter of the conversion solution is 70-100 g, the amount of 2-pyrazinemethanol added is 25-50 g, and the amount of sodium bisulfite added is 10-25 g.
9. The method for preparing a photocatalytic degradation material for treating acephate wastewater according to claim 7, characterized in that: In step c2, the weight of the intermediate B immersed in each liter of the conversion solution is 150-200 g.